A Rare Case of Clival Metastasis in a Patient with Gastric Cancer - Yoshikawa-Kimura, Akie (Intern Med, 2020)
We report a rare case of clival metastasis from gastric cancer. A 73-year-old man with advanced gastric cancer treated with nivolumab as a third-line chemotherapy experienced headache, tongue deviation, and difficulties in speaking clearly. We suspected stroke or brain metastasis, but brain contrast-enhanced magnetic resonance imaging demonstrated a clival mass, diagnosed as clival metastasis from gastric cancer. The tumor could not be identified by plain computed tomography and plain magnetic resonance imaging alone. He received palliative radiotherapy (30 Gy/10 fr); his symptoms improved gradually. Although metastasis from gastric cancer to other organs is common, bone metastases are rare.